Investigating the relationship between student engagement and learning outcomes via flash card technology in Saudi Arabia / Azira Ab Aziz, Noornina Dahlan and Noor Awawdeh - Ab Aziz, Azira; Dahlan, Noornina; Awawdeh, Noor (Faculty of Computer and Mathematical Sciences, 2021)
This investigation attempts to discover if student demographics and student engagement relate to learning outcomes. In higher education research, one of the key concerns is the relationship of student engagement and learning outcomes. The findings can contribute to identify the factors that relate to desirable learning outcomes and the ways to enhance student engagement. Method: This exploratory study examines three undergraduate information systems courses with and without flashcards to learn keywords. A survey acquires data on student demographics and student engagement (study habit, study preference, study source, and learning style). The desirable learning outcomes include academic achievement (course final exam grade), personal achievement (self-esteem), and cognitive skills (knowledge and comprehension). Results: In total, 103 female students participate in this study. The results indicate student demographics and student engagement relate to the desirable learning outcomes.